Relação entre idade cronológica, indicadores de adiposidade corporal e aptidão física relacionada à saúde em meninos e meninas - De Arruda, G. A.; Fernandes, R. A. [UNESP]; Christófaro, D. G D; De Oliveira, A. R. (Centro Andaluz de Medicina del Deporte, 2013)
Objectives. The purpose of this study was to analyze the relationship between adiposity indicators, age and physical fitness related to health. Methods. The sample involved 43 boys and 53 girls. The tests applied were: the Sit-up (S), Modified Pull-up (MP) and Run/Walk (RW) tests. Fat indicators were: Body Mass Index (BMI), subscapular (SB), triceps (TR), and calf (C) skinfolds; the skinfolds sum (Σ) and percentage of fat mass (%F). Results. The results indicated negative correlation between MP and TR, MC, Σ and %F for boys and girls (r = -0,42 a r = -0,52, P ≤ 0,01). There was positive correlation among the S test and age for both groups (r = 0,35, P ≤ 0,05 a r = 0,52, P ≤ 0,01), and negative on the S test with SB, MC and %F for the girls (r = -0,28 a r = -0,29, P ≤ 0,05). Negative correlation also was verified between RW with TR for the boys (r = -0,30, P < 0,05). Conclusion. Age seemed to be related with better performance, and adiposity with weaker performance, mostly in the MP where it is necessary to support their own body mass. Thus, these factors should be considered in the interpretation of results and when establishing criteria for health-related tests with these characteristics. © 2013 Revista Andaluza de Medicina del Deporte.
Relationship between chronological age, adiposity and health-related physical fitness on boys and girls
Keywords: Body mass index; Physical fitness; Skinfolds